2020
DOI: 10.1021/acs.nanolett.0c01707
|View full text |Cite
|
Sign up to set email alerts
|

Trion Emission Dominates the Low-Temperature Photoluminescence of CdSe Nanoplatelets

Abstract: Colloidal nanoplatelets (NPLs) are atomically flat, quasi-two-dimensional particles of a semiconductor. Despite intense interest in their optical properties, several observations concerning the emission of CdSe NPLs remain puzzling. While their ensemble photoluminescence spectrum consists of a single narrow peak at room temperature, two distinct emission features appear at temperatures below ~160 K. Several competing explanations for the origin of this two-color emission have been proposed. Here, we present te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
78
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(100 citation statements)
references
References 38 publications
18
78
0
Order By: Relevance
“…Previous low‐temperature PL studies have shown that a single CdSe NPL only has one band‐edge exciton emission, whereas CdSe NPL stacks upon ethanol addition exhibit an additional PL emission peak in the low‐energy side at a cryogenic temperature. Although several hypotheses [ 154–156 ] have been proposed to interpret the origin of this additional PL peak, phonon line emission, as one of the possible mechanisms, was tentatively proposed to account for the collective effects in the NPL stacks films. [ 157 ] Transient electric birefringence study of CdSe NPLs’ helical structure demonstrated the presence of a dominant in‐plane permanent dipole along with a small amount of out‐of‐plane dipole.…”
Section: Long‐range Controlled Orientation Of Anisotropic Cdse Npl Assembliesmentioning
confidence: 99%
“…Previous low‐temperature PL studies have shown that a single CdSe NPL only has one band‐edge exciton emission, whereas CdSe NPL stacks upon ethanol addition exhibit an additional PL emission peak in the low‐energy side at a cryogenic temperature. Although several hypotheses [ 154–156 ] have been proposed to interpret the origin of this additional PL peak, phonon line emission, as one of the possible mechanisms, was tentatively proposed to account for the collective effects in the NPL stacks films. [ 157 ] Transient electric birefringence study of CdSe NPLs’ helical structure demonstrated the presence of a dominant in‐plane permanent dipole along with a small amount of out‐of‐plane dipole.…”
Section: Long‐range Controlled Orientation Of Anisotropic Cdse Npl Assembliesmentioning
confidence: 99%
“…We analyze the emission spectra of trions in core-only and core/shell NPLs. Negative trions are studied unless otherwise noted, as it is the most frequently reported species in these structures, 23,24,33,34 but the conclusions do not depend on the sign of the charged exciton (see Fig. S2 in the Supporting Information, SI).…”
Section: Resultsmentioning
confidence: 99%
“…In core-only CdSe NPLs, the low temperature photoluminescence is thought to arise from subpopulations of excitons and negative trions. 24,33,46 Very recently, Antolinez and co-workers have reported that the X − emission shows a distinct peak or a shoulder (depending on the film thickness) redshifted from the trion band edge transition. The redshift is ∼ 19 meV and the relative height 15 − 25% that of the main peak.…”
Section: Relationship With Experimentsmentioning
confidence: 99%
See 2 more Smart Citations